(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: This review draws attention to the close interplay between violent criminal behaviour and brain, hormonal functions. Methodology: The presentation of the article is based on the methodology of content analysis and a professional breakdown following the structure of the article. Findings: The authors have undertaken a medical-biological approach to the study of aggression, presenting the prominent roles of the frontal lobe of the brain and of neurotransmitters and hormones in the manifestation of violent behaviour. Value: The study interprets the possible neurobiological reasons behind violent behaviour in a way that is understandable to readers less familiar with science and medicine.